Laporan Hasil Praktik Profesi Asuhan Keperawatan Komunitas di Kp. Pengasinan Rw.03 Kel. Periuk Jaya Kec. Periuk Kota Tangerang - Alfika Safitri; Mugiyanto Mugiyanto; Nuryatul Hasanah; Ely Wahyuni; Novita Sariayu; Cholisa Resmi Sari; Hairul Efendi; Susi Aria Mensi; Lidia Rosaria; Dara Nurhidayati; Dini Trifani; Muhamad Saifudin; Yuli Irawati; Siti Mahdiah; Titi Sabariyah; Rini Handayani; Nunung Sri Haryati (STIKes Ibnu Sina Ajibarang, 2024)
Nursing is a profession that is oriented towards health services with all independent planning or action to help improve the welfare of people's lives. Definitions of community are also many and varied. According to McKenzie et al. (2016) in (Alvian Fabanyo, 2022). A community is a group of people who have similar characteristics. The similarity of these characteristics is determined by location, race, ethnicity, age, occupation, similarity of interest in solving certain problems, results, or other common ties (Alvian Fabanyo, 2022). The aim of this nursing care is to provide an overview of the implementation of community nursing care in the Kp region. Pengasinan RW 03, Periuk Jaya Village, Periuk District, Tangerang City, Banten. Case study design using nursing care. The case study sample used 96 people in Rw. 03. The evaluation stage is an activity to assess the implementation of interventions and implementation that has been implemented at this stage, there is still a lot that needs to be evaluated because it takes a long time, so a follow-up plan is needed with the community in accordance with the existing nursing plan. Meanwhile, short evaluations in the form of verbal and nonverbal responses have been carried out, such as during outreach activities, distributing leaflets, discussions and putting up posters. The existence of good cooperation between students, and community participation as well as support from village officials, cadres, RW/RT and local health centers are very helpful in determining activity criteria.